Mixed infections in children with Mycoplasma pneumoniae pneumonia - Chen, Ling-ling (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2012)
OBJECTIVE: To investigate the incidence and clinical features of mixed infections in children with Mycoplasma pneumoniae (MP) pneumonia